Silicon substituted lithium stannum phosphate ceramic electrolytes: structural, electrical and electrochemical properties / Noriah Ab Wahab …[et al.] - Ab Wahab, Noriah; Dzulkurnain, Nurul Akmaliah; Mustaffa, Nur Amalina; Mohamed, Nor Sabirin (Universiti Teknologi MARA Shah Alam, 2020)
Structural, electrical, and electrochemical properties of silicon (Si) substituted NASICON-structured lithium stannum phosphate, Li1+ySn2P3- ySiyO12 with 0 < y < 1 that was prepared by the low-temperature waterbased sol-gel method has been investigated. From the structural analysis, all samples in the system from y = 0.1 to 0.5 displayed rhombohedral symmetry. The electrical analysis showed that the total ionic conductivity, was increased with the increase of silicon content, y. A high ionic conductivity value of 6.05 × 10-5 S cm-1 exhibited at y = 0.5 with a temperature of 500 °C. Linear sweep voltammetry analysis of the highest conducting sample showed that the sample was electrochemically stable up to 5.1 V. Meanwhile, the ionic transference number value of the sample was 0.99, suggesting that the majority of mobile charge carriers were predominantly due to ions. Thus, from these results, it indicated that silicon substitution in LiSn2P3O12 ceramic electrolytes is significantly enhanced the electrical and electrochemical properties.